Inhibition of the NFATc4/ERK/AKT Pathway and Improvement of Thiol-Specific Oxidative Stress by Dronedarone Possibly Secondary to the Reduction of Blood Pressure in an Animal Model of Ventricular Hypertrophy - Pazó-Sayós, Laia; González, Maria Carmen; Quintana-Villamandos, Begoña (Frontiers in Physiology, 2020)
Untreated chronic hypertension causes left ventricular hypertrophy, which is related to the occurrence of atrial fibrillation. Dronedarone is an antiarrhythmic agent recently approved for atrial fibrillation. Our group previously demonstrated that dronedarone produced an early regression of left ventricular hypertrophy after 14 days of treatment in an experimental study. In this study, we analyze the possible mechanisms responsible for this effect. Ten-month-old male spontaneously hypertensive rats (SHRs, n = 16) were randomly divided into therapy groups: SHR-D, which received dronedarone, and hypertensive controls, SHR, which received saline. Ten-month-old male Wistar Kyoto rats (WKY, n = 8), which also received a saline solution, were selected as normotensive controls. After 14 days of treatment, echocardiographic measurements of the left ventricle were performed, blood samples were collected for thiol-specific oxidative stress analysis, and the left ventricles were processed for Western blot analysis. Dronedarone significantly lowered the left ventricular mass index and relative wall thickness compared with the SHR control group and no differences were observed between the SHR-D group and the WKY rats. Interestingly, the SHR-D group showed significantly decreased levels of p-NFATc4, p-ERK1/2, and p-AKT compared with the hypertensive controls, without statistical differences when compared with the WKY rats. Moreover, the SHR control group showed elevated thiolated protein levels and protein thiolation index compared with the WKY rats. After treatment with dronedarone, both parameters decreased with respect to the SHR control group, until reaching similar levels to the WKY rats. Our study suggests that dronedarone produces inhibition of the NFATc4/ERK/AKT pathway and improvement of thiol-specific oxidative stress possibly secondary to the reduction of blood pressure in an animal model of ventricular hypertrophy..